Research on Innovation of Network Information Security Technology Based on Cloud Computing. Issue 2 (October 2020) - Zhang, Jianshi
Abstract: Cloud computing has become a new network service mode, which can provide a series of resources for many users and carry out intelligent computing according to their needs and daily habits. While technology development brings positive effect, it will also have negative effects. More and more hackers and viruses are trying to invade computers, endangering network security to provide users with storage and data processing services. Based on the widely used environment of cloud computing, this paper studies the innovation of network information security technology with the development of science and technology.